Penerapan Media Permainan Ludo Berbasis Konvensional Terhadap Minat Belajar Bahasa Indonesia Kelas VIII SMP Harapan Ibu Jakarta Islamic School - Nisa, Aprilda Chairun (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study used a descriptive qualitative method with respondent questionnaire data in the form of percentages described in words. The purpose of the study was to determine the influence of the application of ludo game media on the interest in learning Indonesian class VIII at SMP Harapan Ibu Islamic School Jakarta. Meanwhile, the stages in this study are the stages of preparation, implementation, and evaluation of the application of conventional ludo game media. Data collection is carried out by observation and providing questionnaires to students directly. The results of this study showed that respondents from students gave positive responses to the application of ludo games with enthusiasm, pleasure, and enthusiasm in carrying out learning through the game model. From the questionnaire data, the positive responses of participants can be proven in the results of the questionnaire in the form of statements of 1-8. The results of student responses showed in a percentage that more than 50% by agreeing with the application of ludo games that can foster interest in learning in a positive direction.